Comparing Pears to Apples: Unlike Dogs, Cats Need Habituation before Lab Tests - Stefania Uccheddu; Ádám Miklósi; Sarolt Gintner; Márta Gácsi (Animals, 2022)
Research on the socio-cognitive skills of different species often benefit from comparative experiments, however, the ecology of the species and development of the individuals may differently determine how they react to the same test situation. In this study, our aims were twofold: to observe and compare the spontaneous behaviour of companion cats and dogs in the same novel environment, and to habituate them (if needed) to the novel environment in the presence of their owners and an unfamiliar experimenter. The behaviour of 62 family cats, 31 experienced (which had the opportunity to meet strangers and explore unfamiliar places) and 31 inexperienced cats, and 27 family dogs was compared in an unfamiliar room. The subjects’ behaviour was coded during the first five minutes in the presence of two passive persons, their owners, and an unfamiliar experimenter. Then, based on a set of rules, first the owner, and then the experimenter tried to initiate interactions with the subjects and the subjects’ willingness to interact was evaluated. To pass the habituation test, subjects were expected to play with the experimenter or accept food from them. All dogs passed the test on the first occasion, while almost 60% of the cats failed. The cats’ experience did not play a significant role, in fact, younger cats passed more easily. We found marked differences between dogs and cats in all behavioural variables; compared to dogs, cats spent more time crouching and close to their box, while less time exploring or close to the owner. We did not find a difference in the cats’ behaviour based on their experience. Our results support the hypothesis that unlike dogs, cats need extensive habituation in a novel environment. This could partially be explained by the difference in the ecology and/or domestication process of the species, although developmental effects cannot be excluded. Our findings have fundamental consequences not only for the considerations of the testability of cats and on the interpretation of their data collected in the laboratory, but in a more general sense on developing comparative experiments.